The Role of Physical Techniques on the Preparation of Photoanodes for Dye Sensitized Solar Cells - Shideh Ahmadi; Nilofar Asim; M. A. Alghoul; F. Y. Hammadi; Kasra Saeedfar; N. A. Ludin; Saleem H. Zaidi; K. Sopian (International Journal of Photoenergy)
Dye sensitized solar cells (DSSCs) have attracted numerous research, especially in the context of enhancing their efficiency and durability, due to the low-cost and environmentally friendly nature of photovoltaic (PV) technology. The materials in DSSCs are vital towards the realization of these goals, since many of the important components are influenced by their respective preparation and deposition methods. This review aims to detail the research and development aspects of the different physical methods with the purpose of evaluating their prospects and corresponding limitations. The diversity of consideration and criteria includes thin film applications, material characteristics, and process technology that need to be taken into account when selecting a specific deposition method. Choosing a deposition method is not as simple as it seems and is rendered quite complicated due to various factors. Usually, a researcher will evaluate techniques based on factors such as the different preparations and deposition technology with materials’ and substrates’ type, specified applications, costs, and efficiencies.